2021
DOI: 10.1097/md.0000000000023532
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Baduanjin on glucose and lipid metabolism in diabetic patients

Abstract: Background: Baduanjin is an ancient technique of physical and breathing exercises (Dao Yin). This technique is divided into eight sections and each section is a motion, so it is called “Baduanjin”. It is practice without equipment, simple and easy to learn, whose effect is significant leading to good fitness effect. Diabetes mellitus is a chronic metabolic disease. Clinical studies have reported that Baduanjin can affect the metabolism of blood glucose and blood lipid in diabetic patients, but the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
(8 reference statements)
3
6
0
Order By: Relevance
“…In line with our current findings, both animal models 37,42 and patient studies [43][44][45] have previously shown that dietary interventions that reduce body weight also improve metabolic disorders, including T2D and its complications. Moreover, we found that all three dietary interventions ameliorated glycemic status, consistent with other reports in db/db mice 46,47 and in patients with T2D.…”
Section: Discussionsupporting
confidence: 91%
“…In line with our current findings, both animal models 37,42 and patient studies [43][44][45] have previously shown that dietary interventions that reduce body weight also improve metabolic disorders, including T2D and its complications. Moreover, we found that all three dietary interventions ameliorated glycemic status, consistent with other reports in db/db mice 46,47 and in patients with T2D.…”
Section: Discussionsupporting
confidence: 91%
“…Neck pain is a common condition that reduces the individual quality of life and causes economic loss and mental burden, gaining increasing concerns (6,51). Baduanjin is an ancient traditional Chinese medicine method that regulates and improves the respiratory, metabolic, digestive, circulatory, and motor systems (52)(53)(54). As an adjunctive treatment, in recent years, Baduanjin has gradually been used to treat NP in the middle-aged and elderly group (7,55).…”
Section: Discussionmentioning
confidence: 99%
“…TCEs are slow, relaxing, and systematic, and therefore suitable for physically weak patients. By correcting body posture and movements, adjusting breathing patterns, and maintaining stillness of mind, a wide array of natural self-regulatory/self-healing mechanisms are activated to stimulate the balanced release of endogenous neurohormones (24,25), promote blood flow, strengthen muscles and bones, and consolidate minds (26)(27)(28)(29). Therefore, TCEs simultaneously improve physiological as well as psychological status of CHD patients, proving to be a low-risk, promising intervention (30,31).…”
Section: Introductionmentioning
confidence: 99%